Prescribing Pattern of Gliclazide, Metformin and Combination Therapy with Insulin in UAE - Sabrina Ait Gacem, Zainab Tehami, Maryam Mazrouai, Mohamed Shamssain (Journal of Applied Pharmaceutical Science, 2018)
Diabetes Mellitus (DM) is characterized by the inability of the body to process sugar. Glycemic control is important in the management of diabetic patients; therefore, there is a particular concern towards the insufficient management of oral drug therapy and delayed insulin therapy initiation. The current study was made to observe the status of anti-diabetic drugs’ prescription pattern. This is a cross-sectional, questionnaire-based survey study, which was conducted over a period of February 2014 to May 2014 and it was carried out in Ajman. A convenient sample comprising a total of (213) diabetic participants of 18 years old and above. A self-administered bilingual questionnaire was used as a tool to collect data and the results were analyzed using Microsoft Excel. The prescribing trend was found to be monotherapy (43% Metformin, 33% Insulin and 17% Gliclazide) and (7%) of participants used a combination therapy of Metformin and Insulin. The study reflected that the prescribing trend in the enrolled participants was mainly monotherapy and among the cardiovascular complications reported that can cause major threat was hypertension. Similar other studies indicate that the compliance with medication, exercise and avoiding risk factors are very important to prevent complications.
Keywords: Diabetes mellitus, Insulin, Metformin, Gliclazide.